Degradation of mechanical properties of laminates with multi delaminations - Tu, Wenge. (2008)
This report present a numerical model for rapidly computing the critical loads of beams with multiple delaminations and to analysis the buckling behaviour of laminated composite beam under in-place compression. This study is focused on beam has two unequal length parallel delaminations with one enveloping the other.